Biophysical Interface of Anti-Matter for Virtual Living in Real World: A Reality in Chemical Converted in Parallel Worlds - (:unkn) unknown (AMG Transcend Association, 2021)
We are going to discuss biology and the biophysical phenomenon of the anti-matters, both experimentally and theoretically or philosophically. Anti-matter is used to treat cancer and thymine dimer problems due to UV radiation. Positrons are beamed through tissue at such velocity that they do not annihilate until they encounter cancer cells. Formed gamma rays damage the cancer tissue. Nowadays, anti-matter is used in positron emission tomography (PET). In evolutionary biology, where we see evidence that consciousness has emerged in at least humans, lifeforms can self-organize to exhibit collective emergent super-consciousness. In this work, we are looking at an ontological explanation of the relationship between the results obtained with the Ecology. The proton transfer mechanism is a critical phenomenon that is related to the acid-base characteristics of the nucleobases in Watson–Crick base pairs. They exhibited a strong probability for protons to change place within the hydrogen bond due to quantum tunneling, which will alter the genetic code and cause mutations. These mutations could be the cause of several diseases such as cancer. Probably, the quantum tunneling effect (such as proton transfer) appears in micro parallel worlds.
Keywords: 3. Good health